2010
DOI: 10.3174/ajnr.a2398
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Rupture Following Treatment with Flow-Diverting Stents: Computational Hemodynamics Analysis of Treatment

Abstract: BACKGROUND AND PURPOSE:Flow-diverting approaches to intracranial aneurysm treatment had many promising early results, but recent apparently successful treatments have been complicated by later aneurysm hemorrhage. We analyzed 7 cases of aneurysms treated with flow diversion to explore the possible rupture mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
317
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(331 citation statements)
references
References 15 publications
11
317
2
1
Order By: Relevance
“…8,26 Although hearing is not ubiquitously sacrificed, it is now well known that this approach does pose a significant threat to postoperative hearing function. 9,52 In contrast, the modern posterior petrosal approach entails a presigmoid retrolabyrinthine exposure with exceedingly high rates of preservation of postoperative hearing, as demonstrated in this report and many others. 1,33,48,50 In comparison with the anterior petrosal approach, an anatomical study revealed that the posterior petrosal approach afforded an additional 6 mm of caudal exposure below the floor of the sella, essentially to the level of the upper jugular tubercle.…”
Section: Posterior Petrosal Approachmentioning
confidence: 84%
See 1 more Smart Citation
“…8,26 Although hearing is not ubiquitously sacrificed, it is now well known that this approach does pose a significant threat to postoperative hearing function. 9,52 In contrast, the modern posterior petrosal approach entails a presigmoid retrolabyrinthine exposure with exceedingly high rates of preservation of postoperative hearing, as demonstrated in this report and many others. 1,33,48,50 In comparison with the anterior petrosal approach, an anatomical study revealed that the posterior petrosal approach afforded an additional 6 mm of caudal exposure below the floor of the sella, essentially to the level of the upper jugular tubercle.…”
Section: Posterior Petrosal Approachmentioning
confidence: 84%
“…9,34 Employed as a necessary means to curb thromboembolic complications, requisite dual antiplatelet therapy relatively contraindicates usage of endovascular stent placement in instances of acute subarachnoid hemorrhage. 58,60 In this setting, plagued by the specter of early rerupture, the cerebrovascular neurosurgeon must safely expose these complex aneurysms and adjacent vital perforators while navigating an edematous, "angry" brain.…”
mentioning
confidence: 99%
“…For example, the authors in [6] ordered the equations element by element. In the Jacobian matrix we use the symbols K for the kinematic equation (15) in the solid and on the fluid-solid interface, A for the kinematic ALE displacement equation (22) in the fluid, S for the momentum equation (7) in the solid, I for the momentum equation (9) on the fluid-solid interface, F for the momentum equation (16) in the fluid, V for the continuity equation (8) in the solid, W for the continuity equation (17) in the fluid. The Jacobian has the following block structure, and the order of the variables is listed at the top of the matrix.…”
Section: Structure Of the Jacobianmentioning
confidence: 99%
“…To resolve such meshing difficulties, two possible options can be explored: adaptive embedding techniques and porous medium modeling. With the former approach, vessel walls are treated with body-fitted unstructured grids, and stents are embedded in the grids; moreover, adaptive meshing refinement is performed near the stents ( [10], [8]). A more recent technique simulates the effect of a FD through the use of a porous medium layer ( [3], [33], [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decades, several groups have been using computational methods in order to extract parameters explaining aneurysmal formation or predicting rupture probabilities [16]- [18]. However, those investigations mainly focus on single aneurysm models using various assumptions and leading to controversial discussions [19].…”
Section: Introductionmentioning
confidence: 99%